2020
DOI: 10.3390/ijms21165878
|View full text |Cite
|
Sign up to set email alerts
|

A Novel R2R3-MYB Transcription Factor PqMYB4 Inhibited Anthocyanin Biosynthesis in Paeonia qiui

Abstract: Paeonia qiui is a wild tree peony native to China. Its leaves show a clear purple-red color from the germination to the flowering stage, and it has high leaf-viewing value. A MYB transcription factor gene, designated as PqMYB4, was isolated from leaves of P. qiui based on transcriptome datas. The full-length cDNA of PqMYB4 was 693 bp, encoding 230 amino acids. Sequence alignment and phylogenetic analysis revealed that PqMYB4 was a R2R3-MYB transcription factor clustered with AtMYB4 in Arabidopsis thaliana. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 42 publications
0
6
0
1
Order By: Relevance
“…As one of the largest TF families in higher plants, MYB TF involves diverse biological, functional and structural processes [28]. Several studies showed that flavonoid-related R2R3-MYB repressors had been isolated in various plants, such as PqMYB4 [29], AtMYBL2 [30] and PpMYB18 [31]. The study confirmed that BcMYB44 belonged to R2R3-MYB and had the same two MYB domains and transcriptional suppression of the LSLSL subdomain with other closely related MYB44 proteins, which was consistent with the findings of Wei et al [11].…”
Section: Discussionmentioning
confidence: 99%
“…As one of the largest TF families in higher plants, MYB TF involves diverse biological, functional and structural processes [28]. Several studies showed that flavonoid-related R2R3-MYB repressors had been isolated in various plants, such as PqMYB4 [29], AtMYBL2 [30] and PpMYB18 [31]. The study confirmed that BcMYB44 belonged to R2R3-MYB and had the same two MYB domains and transcriptional suppression of the LSLSL subdomain with other closely related MYB44 proteins, which was consistent with the findings of Wei et al [11].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, some flavonoid biosynthesis-related R2R3-MYBs were found in P. qiui through transcriptome sequencing [ 30 ]. Among them, two R2R3-MYBs (PqMYB113 and PqMYB4) were isolated, and their biological functions were verified in anthocyanin biosynthesis [ 31 , 32 ]. In this study, another flavonoid (flavonol) biosynthesis activator, PqMYBF1 from the leaves of P. qiui , was characterized, and the biological function of PqMYBF1 was investigated using genetically modified tobacco, which will enrich our knowledge about tree peony leaf color variation in spring.…”
Section: Introductionmentioning
confidence: 99%
“…MYB plays an important role in regulating plant cell growth and development, abiotic stress and biotic stress, and metabolic reactions. The regulatory role of MYB family members in plant fruit traits mainly includes the direct regulation of pericarp thickness and the regulation of the active ingredients in fruit [28][29][30]. Based on a genome study of the Guire No.1 variety [23], a transcriptome analysis was performed of macadamia nut varieties A38, Guire No.1, and HAES900, with significant differences in pericarp thickness.…”
Section: Discussionmentioning
confidence: 99%